Chapter 1 Metaphor, transformation, and transdisciplinarity - Sage, Colin (Taylor & Francis, 2022)
"This book offers an eclectic range of transdisciplinary insights into the role of metaphor, myth and fable in shaping our understanding of the world and how we interact with it and with each other. Drawing on innovative perspectives from widely different fields, this book explores how metaphor might facilitate and underpin transformative change towards environmental, ecological and societal sustainability. It illustrates the ways in which contemporary metaphors lock us into patterns of thinking, modes of behaviour and styles of living that reproduce and accentuate our current socio-environmental problems. It sets itself the task of finding new metaphors and myths that might help move us towards sustainability as societal flourishing. By examining the use of metaphor in diverse fields such as energy use, the food system, health care, arts and the humanities, it invites the reader to reflect on the deep-seated influence of language in general, and metaphor in particular, in shaping how we understand and act upon the world. Re-imagining the use of language in framing both the problems we face and the solutions we devise, this novel contribution is a vital source of ideas for those aiming to change how we think and act in pursuit of more sustainable futures."